2020
DOI: 10.1371/journal.pgen.1008562
|View full text |Cite
|
Sign up to set email alerts
|

Mutations on ent-kaurene oxidase 1 encoding gene attenuate its enzyme activity of catalyzing the reaction from ent-kaurene to ent-kaurenoic acid and lead to delayed germination in rice

Abstract: Rice seed germination is a critical step that determines its entire life circle, with seeds failing to germinate or pre-harvest sprouting both reduce grain yield. Nevertheless, the mechanisms underlying this complex biological event remain unclear. Previously, gibberellin has been shown to promote seed germination. In this study, a delayed seed germination rice mutant was obtained through screening of the EMS induced mutants. Besides of delayed germination, it also shows semi-dwarfism phenotype, which could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…2004 , Chen et al. 2019 , Zhang et al. 2020 ), while OsKO4 (CYP701A8) hydroxylates ent -kaurene and related diterpenes at the 3α position, which is in close proximity to C-19 ( Wang et al.…”
Section: Formation Of C 20 -Gibberellinsmentioning
confidence: 99%
See 1 more Smart Citation
“…2004 , Chen et al. 2019 , Zhang et al. 2020 ), while OsKO4 (CYP701A8) hydroxylates ent -kaurene and related diterpenes at the 3α position, which is in close proximity to C-19 ( Wang et al.…”
Section: Formation Of C 20 -Gibberellinsmentioning
confidence: 99%
“…2012 ). By coupling the N-terminal regions to GFP, Zhang et al. (2020) showed that OsKO2, similar to AtKO, is located in the plasmid outer membrane, whereas OsKO1 is present in the plastid and endomembranes.…”
Section: Formation Of C 20 -Gibberellinsmentioning
confidence: 99%
“…The previous studies reported that gibberellins (GAs) play important roles in seed germination, stem elongation, and flower development (Yamaguchi and Kamiya 2000 ; Olszewski et al 2002 ). Recent studies demonstrated that genes involving in GA synthesis, OsGA20ox1 , OsGA20ox2 and OsKO1 promotes germination and enhances plant height in rice (Abe et al 2012 ; Ye et al 2015 ; Zhang et al 2020 ), while QTLs for seedling height and seed dormancy co-located with OsGA20ox1 (Abe et al 2012 ) and OsGA20ox2 (Ye et al 2015 ), respectively. Therefore, it could be possible that some LTG QTLs enhance seed germination under low temperature, and also contribute to increase in plant height, such QTLs could not be used in rice breeding for direct-seeding due to the risk of lodging.…”
Section: Introductionmentioning
confidence: 99%
“…Good candidates for future studies might also be other genes in the same region encoding an Ent-kaurene oxidase and two B3 domain proteins, all involved in GA biosynthesis: the latter are regulating factors of the pathway in which the former is a key enzyme, and it is reported that suppressive mutations in the coding region of both genes cause a delay in seed germination and seedling development [94,95].…”
Section: Seed Emergency Indexmentioning
confidence: 99%